Offences under Road Transport Act 1987: a comparative analysis between the day fine system and the fixed financial system / Fatin Nadira Abdul Wahab … [et al.] - Abdul Wahab, Fatin Nadira; Zulkifli, Muhammad Zahier; Putra Sulaiman, Mohamad Nurhidayat; Nik Hilmi, Nik Muhammad Syafiq (2013)
The purpose of this research is to suggest the implementation of the day fine system for compoundable offences under the Road Transport Act 1987 in Malaysia. Day fine is a unique system since the amount of fine is varied according to the offender's financial background and it has been adopted in many Western countries. Under the Road Transport Act 1987, there are some traffic offences which are punishable with compound. Compound is a financial punishment in which the amount of the fine imposed for an offence is fixed. Thus, each offender regardless their financial status, will be imposed the same amount of fine for committing the same type of an offence. However, the fixed financial system fails to reduce the rate of the accidents and traffic offences due to the inefficiency of the fixed fine system in promoting the deterrence and punitive effect among the traffic offender. Therefore, we would like to suggest the implementation of the day fine system as an initial step towards the reduction of traffic offences and accidents in Malaysia. We managed to identify the weaknesses of the fixed fine system by way of interview, case study and observing the current situation related to traffic offences that happened in Malaysia. Furthermore, we made a comparative study with countries that adopt the day fine system to determine the efficiency of such system. In conclusion, the day fine system is proven to be an effective mechanism in reducing the rate of traffic offences and accidents in Malaysia.